ЗАЩИТА ОТ ДУХОВНОЙ МАРГИНАЛИЗАЦИИ – СПОСОБ СОХРАНЕНИЯ НАЦИОНАЛЬНО-КУЛЬТУРНОГО НАСЛЕДИЯ ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article analyzes the processes taking place in the spiritual sphere in the current conditions of rapid globalization, and talks about the nature of spiritual marginalization, which has a negative effect on the formation of the spirituality of young people. The need for a mechanism to protect the minds of young people, the importance of educating a spiritually mature person and a healthy generation is highlighted. There was talk about the importance of protecting against the moral decline that leads to deep negative consequences and the moral marginalization that causes it.